2018
DOI: 10.1177/1475921718756602
|View full text |Cite
|
Sign up to set email alerts
|

Tire health monitoring using the intelligent tire concept

Abstract: Tire durability plays an important role in road transportation safety. Damaged tires can cause vehicle instability and create potential traffic accidents. To study the potential of using the intelligent tire concept for health monitoring of the tire, a computational method for defect detection in tire structure was developed. Comparing the trend of acceleration signals for the undamaged and damaged tires can reveal information about the crack length and location around the tire circumference. To accomplish thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…It is used to predict crack locations using acceleration signals obtained from a triaxial accelerometer attached to the tire inner liner. It has been observed that the radial component of the acceleration signal plays a key role in the defect detection of smart tires [4]. With the explosive development of smart wearable devices, the problems of massive energy waste and environmental pollution caused by electronic waste need to be solved urgently.…”
Section: Related Workmentioning
confidence: 99%
“…It is used to predict crack locations using acceleration signals obtained from a triaxial accelerometer attached to the tire inner liner. It has been observed that the radial component of the acceleration signal plays a key role in the defect detection of smart tires [4]. With the explosive development of smart wearable devices, the problems of massive energy waste and environmental pollution caused by electronic waste need to be solved urgently.…”
Section: Related Workmentioning
confidence: 99%
“…Rosu et al used the finite element tire model to predict the temperature change inside the tire until the time of takeoff of the airplane tire [ 11 ]. Behroozinia et al proposed the possibility of detecting cracks inside the tire through analysis of the acceleration signal measured inside the tire using rolling simulations of the finite element tire model [ 12 ].…”
Section: Related Materialsmentioning
confidence: 99%
“…Filled elastomer materials (FEM) continue to attract industrial interest due to their exceptional properties that find application in various engineering fields (Behroozinia et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%